Obsession with future food. Reflections on the role of time in food design. - Massari, Sonia (Revista Latinoamericana de Food Design, 2020)
We are currently living in the past and the future at the same time. We are living in a moment of uncertainty that is seemingly suspended in an unstable present. This paper aims to reflect on the effect of time on the combination of food and design. The work of food designers intrinsically incorporates the idea of the future. We could say, to use a provocative expression, that food designers are obsessed with future food. While the term “sustainability” is not yet a global priority, Covid-19 has brought to light its oldest value, that is, one linked to the idea of time. Sustainability is in fact defined as the ability to maintain in the long term the ecological processes that happen within an ecosystem. For this motive, “sustainable development” means taking responsibility, in particular towards the next generations”.